"The Company You Keep": Unpacking a Measurement Model of Social Network Interdependence. Issue 1 (2nd January 2019) - Stein, James
ABSTRACT: Both classical and contemporary interpersonal theories have identified the social networks surrounding a couple as integral players in relational development and maintenance. The current project extends this line of research by designing (Study 1) and implementing (Study 2) a measurement of social network interdependence. Scales of network interference and facilitation are developed and probed using exploratory and confirmatory factor analysis. Results support distinct measures of network interference and facilitation. Invariance between differencing samples is tested for using multi-factor CFA. Results showed that measures of network interference and facilitation significantly vary between married and dating couples. Finally, convergent, divergent, and concurrent validity is tested for subscales using variables in relational turbulence theory. Results demonstrate that network interference and facilitation uniquely impact outcome variables above and beyond experiences of partner interference and facilitation. Results are discussed in terms of theory development.